Metric indexing for content-based medical image retrieval (2008)
The paper proposes an indexing method for fast content-based retrieval in an image repository. The method is based on a metric-indexing strategy that avoids calculating the distance from the query to all the images in the repository. The proponed indexing method is tested on a pathology image Collection comparing its performance against sequential scanning indexing. The results show that the metric indexing method improves the access time by a factor of 10, without a signi?cant sacr i?ce on precision.